Architectural drawing - Field, Wooster Bard.; French, Thomas E. (New York : McGraw Hill Education, 1922)
An exhaustive treatment of the subject of Architectural Drawing presents so many ramifications that, to cover them fully, several volumes of text and many expensive plates are required. Almost without exception these books and portfolios each deal with but one phase of the subject and go into that at some length.
Introduction -- I. Graphic methods of representation -- II. Drawing instruments and their use -- III. Geometric methods -- IV. Preliminary sketches -- V. Scale drawings -- VI. Detail drawings -- VII. The orders of architecture -- VIII. The acanthus leaf -- IX. Mouldings -- X. Architectural lettering -- Reference books -- Architectural and building terms -- Alphabetical index.
Includes bibliographical references and index.
Keywords: LETTERING